2000
DOI: 10.1046/j.1525-1497.2000.02329.x
|View full text |Cite
|
Sign up to set email alerts
|

Problems in recruiting community-based physicians for health services research

Abstract: Physician personal contact and friendship networks are powerful tools for recruitment. Participation rates might improve by including HMO and minority physicians in the recruitment process. Investigators should transfer as much of the study burden from participating physicians to project staff as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
225
5
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(248 citation statements)
references
References 20 publications
14
225
5
4
Order By: Relevance
“…First, the overall survey response was somewhat low, but comparable to other provider surveys and response rates in this range have not been shown to be associated with increased responder bias. [31][32][33] In our survey, respondents did not differ from non-responders in demographic characteristics. 7 Furthermore, the majority of respondents were involved in supervision of trainees, allowing the current analysis.…”
Section: Resultsmentioning
confidence: 99%
“…First, the overall survey response was somewhat low, but comparable to other provider surveys and response rates in this range have not been shown to be associated with increased responder bias. [31][32][33] In our survey, respondents did not differ from non-responders in demographic characteristics. 7 Furthermore, the majority of respondents were involved in supervision of trainees, allowing the current analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, having a medical peer telephone a GP's surgery greatly simplified access to the practice, a finding that has been previously noted (Veitch et al 2001;Sellors et al 2002;Ellis et al 2007). Reasons why the medical-peer approach works is the ability to pass the practice 'gatekeeper', usually a receptionist, because of their respect and credibility (Heywood et al 1995) and the strength of their personal networks and relationships (Asch et al 2000). A potential drawback of this approach is that GPs may find it hard to say no to a peer at the beginning with time then wasted on a participant who later withdraws (Goodyear-Smith et al 2009).…”
Section: Discussionmentioning
confidence: 85%
“…For example, a survey of published UK primary care trials found that only a minority of trials successfully recruited the required number of participants within the projected timeline (Bower et al 2007). Time constraints due to other commitments like audits and mass vaccinations can often hinder doctors' participation in research (Asch et al 2000;Rosemann and Szecsenyi 2004;Minas et al 2005;GoodyearSmith et al 2009) Australian GPs do not rate financial rewards as a reason to join a research project; however, financial incentives can support a practice's loss of time. There are also project-related and topic-related reasons why GPs do not participate, such as an overly complex research design or a disease area that is considered too sensitive, such as childhood obesity (Jones et al 2011(Jones et al , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of researchers being known to prospective FP participants has been cited by others, even to the point of personal contact and friendship networks [36,37]. Some have suggested that research teams might foster and capitalize on this by using researchers and physicians to do the recruiting [14,36], but the practicality of this from a time or financial compensation point of view has been well noted [4,36]. On the other hand, research funding agencies might need to reconsider their common predominant practice of not providing some financial compensation for researchers' time spent attempting to recruit.…”
Section: Recruitment Of Physiciansmentioning
confidence: 99%